Analisis Kepuasan Petani Sebagai Mitra Kerja Pengelola Daun Talas Beneng Alternatif Pengganti Tembakau Berdasarkan Pola Kemitraan Usaha (Studi Kasus PT. Santy Abadi Mandiri) - Oktavia, Nanda Resti Nur; Pratama, Maulana Agung (Jurnal Kompetitif Bisnis, 2024)
This study aims to identify and analyze the pattern of partnership and the satisfaction of farmers who partner with PT. Santy Abadi Mandiri. This type of research is descriptive research using a qualitative approach. Data collection techniques are observation, interviews and documentation. The results showed that the partnership pattern of PT. Santy Abadi Mandiri and partner farmers run a partnership using the plasma core partnership pattern, according to the following characteristics: the core company provides guidance to the partner group, buys crops from the partner group, the partner group cultivates from start to harvest, the core company and partner groups have rights and obligations. In addition, partner farmers are satisfied that they have collaborated with PT. Santy Abadi Mandiri, partner farmer satisfaction includes profits which are divided into 3 supporting factors, namely coaching, production facilities and cooperation contracts. The company provides the best service to partner farmers. The partnership carried out between the core company and the partner group is in accordance with the cooperation contract that has been made together.